Embodied Storytelling: Loss and Bereavement, Creative Practices, and Support. (October 2015) - Letherby, Gayle; Davidson, Deborah
Art, music, literature, and drama are acknowledged to have a place in the embodied experience of bereavement and increasingly are also utilized for the collection and presentation of data in the social sciences and humanities. Such work tells us much about ourselves as individuals and about our relationships with others. The concept of griefwork, which acknowledges and values the collective work the bereaved do with others, is one way to frame such endeavors during bereavement. Here, we outline some of our individual, and yet connected, creative work with reference to both our own experiences of loss and our relationship with each other. Specifically, we reflect on Deborah's development of an online community for people with commemorative tattoos and Gayle's exploration of new ways of writing (fiction or faction). We share examples from each project and reflect on their significance to the embodied experience of bereavement.